Dermal, but not Epidermal, Immune Reaction in Cutaneous Spiruroid Larva Migrans: Involvement of Basophils in Dermal Interleukin-33 and Thymic Stromal Lymphopoietin Expression - Takashi Hashimoto; Satoshi Okuno; Manami Okuzawa; Takahiro Satoh (Medical Journals Sweden, 2022)
Abstract is missing (Short communication)